Transplanted Human Oligodendrocyte Progenitor Cells Restore Neurobehavioral Deficits in a Rat Model of Preterm White Matter Injury - Wang, Xiaohua; Zang, Jing; Yang, Yinxiang; Lu, Siliang; Guan, Qian; Ye, Dou; Wang, Zhaoyan; Zhou, Haipeng; Li, Ke; Wang, Qian; Wu, Youjia; Luan, Zuo (Frontiers in Neurology, 2021)
Background: Preterm white matter injury (PWMI) is a common brain injury and a leading cause of life-long neurological deficits in premature infants; however, no effective treatment is available yet. This study aimed to investigate the fate and effectiveness of transplanted human oligodendrocyte progenitor cells (hOPCs) in a rat model of PWMI. Methods: Hypoxia-ischemia was induced in rats at postnatal day 3, and hOPCs (6×105 cells / 5 μL) were intracerebroventricularly transplanted at postnatal day 7. Neurobehavior was assessed 12 weeks post-transplant using the CatWalk test and Morris water maze test. Histological analyses, as well as immunohistochemical and transmission electron microscopy, were performed after transcardial perfusion. Results: Transplanted hOPCs survived for 13 weeks in PWMI brains. They were widely distributed in the injured white matter, and migrated along the corpus callosum to the contralateral hemisphere. Notably, 82.77 ± 3.27% of transplanted cells differentiated into mature oligodendrocytes, which produced myelin around the axons. Transplantation of hOPCs increased the fluorescence intensity of myelin basic protein and the thickness of myelin sheaths as observed in immunostaining and transmission electron microscopy, while it reduced white matter atrophy at the level of gross morphology. With regard to neurobehavior, the CatWalk test revealed improved locomotor function and inter-paw coordination after transplantation, and the cognitive functions of hOPC-transplanted rats were restored as revealed by the Morris water maze test. Conclusions: Myelin restoration through the transplantation of hOPCs led to neurobehavioral improvements in PWMI rats, suggesting that transplanting hOPCs may provide an effective and promising therapeutic strategy in children with PWMI.